Peran Teknologi dalam Peningkatan Kualitas Pembelajaran PAI MTS Darul Ulum Waru - Febrian, Rafico Rifki (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study explores the role of technology in improving the quality of Islamic Religious Education (PAI) learning at Mts Darul Ulum Waru. Technology facilitates access to diverse and interactive learning resources, improves learning evaluation, and supports personal and collaborative learning. The main advantages of technology include increased student motivation, wide access to learning resources, and better communication between students and teachers. In addition, technology enables distance learning which is crucial during situations such as the pandemic. However, there are some disadvantages, such as dependence on technology which can cause disruption and gaps in access among students. Excessive use can also reduce students' social interaction and critical thinking skills. Therefore, a balance is needed in the use of technology to maximize its benefits. Technology has great potential to improve the quality of PAI learning at Mts Darul Ulum Waru, but it must be used wisely.